EDUKASI KESEHATAN ALAT REPRODUKSI MENGGUNAKAN MEDIA PAKEM BRAILLE DI MTS YAKETUNIS YOGYAKARTAEDUKASI KESEHATAN ALAT REPRODUKSI MENGGUNAKAN MEDIA PAKEM BRAILLE DI MTS YAKETUNIS YOGYAKARTA - Novia Indah Permatasari Putri Mahenu; Birgita Elsia Setiarini; Familia Putri Wulandari; Fransisca Wahyu Indriastuti; Klemen Wahyu Kurniadi; Florentinus Dika Octa Riswanto (Universitas Sanata Dharma, 2018)
The limitations of science and students' awareness of reproductive health causes such students susceptible to various diseases caused by viruses, fungi, or bacteria. This program aims to provide education about